Case Report: Rare Bladder Injury During Cesarean Section - Ali Tavoosian (Urology Research Center, 2020)
Introduction Bladder injury is an urgent emergency case requiring urgent treatment in order to restore the normal function of the urinary system. Case presentation Here we present a 38-year-old woman with a history of primary infertility with a twin pregnancy following in vitro fertilization (IVF). Because of the high adhesion, the anterior wall of the bladder cut transversely instead of the anterior wall of the uterus. In this case of twin cesarean section, the anterior wall, posterior wall, and uterine wall were opened. The twins were removed from the bladder by two incisions and then the posterior and anterior wall of the bladder were repaired by an expert urologist as well as the uterus followed by medication by anticholinergic and antibiotics. This case report emphasizes the essential roles of bladder emergency repair in restoring the normal function of the urinary system. Conclusions Bladder injury is the most common complication during gyneco-genital surgery. Most of this damage is intraperitoneal that needs repair during the surgery and prolonged bladder catheterization.